Decolonial Sketches and Intercultural Approaches to Truth: Corporeal Experiences and Testimonies of Indigenous Women in Colombia (2020)
This article explores the corporeal and testimonial memories of a group of female indigenous ex-combatants and victims in the Colombian Caribbean and Amazon. Although these groups have often been analyzed in the transitional justice literature, our primary objective is to analyze two local processes for retrieving indigenous women's memories and possible feminist participatory action research methodologies in the Colombian postconflict context. We examined empowering intercultural and intersectional methodologies to promote the political participation of indigenous women - both 'victims' and 'perpetrators' - in the Colombian Truth Commission implemented after the peace agreement was enacted. We explain how participatory action research should be used, including techniques such as indigenous women's body mapping, creating testimonial spaces and conducting ethnographic observations. The article is based on a transitional justice 'from below' perspective as well as local transitional justice practices. © 2020 The Author(s).